The role of national museums in South Africa: A critical investigation into Iziko Museums of South Africa focusing on the representation of slavery - Strydom, Carlyn (African Studies, 2018)
This thesis is concerned with the ways in which museums have been used as vehicles to convey notions of the nation. It looks specifically at the Iziko Museums of South Africa's social history sites that deal with the subject of slavery. It is concerned with the absence of a narrative of slavery at Iziko museums before the demise of Apartheid and looks the historical and socio-political changes that lead to its emergence in South African historical consciousness. It is a study of the history of museums as well as the ways in which history has been used in museums. It looks at the ways Iziko, as a national museum, has guarded and promoted ideas of the nation as decided by the state. The thesis examines with the ways in which the museum has transformed since its inception in the colonial period up to the present day. The time period investigated is 1855 to 2016. Guiding questions for the thesis are: for what purpose were museums created in South Africa; what are the implications of colonial practice on the ways in which they functioned; why has the history of slavery has been disavowed in South African historical consciousness; what led to the rise of the study of slavery in South Africa; what has the emergence of the new museology meant for museum practice; how have heritage studies transformed the South African historical landscape. The thesis begins with a theoretical literature overview of museums more generally and its links with power and representation and the colonial regime. It then moves on to investigate the origin and history of Iziko museums by working through published literature on the subject, unpublished materials, other institutional materials found in the Iziko archive and interviews conducted with past and current employees. It then looks takes an historical survey of South African historiography and its exclusion of the history of slavery and later the emergence of such a narrative. Lastly it looks at how the nation has been narrated by the state after Apartheid and how the museum responded to the new dispensation. The thesis concludes that Iziko museums have transformed over the last two centuries in terms of the subject matter it studies. Museological activity has been diversified to include a range of subjects hitherto ignored in South African public consciousness due to the legacy of both colonialism and Apartheid. Most importantly it shows that the museum has continually responded to concepts of the South African nation and that national museums are inextricably tied to the nation-state.